Crambe (Crambe abyssinica Hochst): A Non-Food Oilseed Crop with Great Potential: A Review - Dulan Samarappuli; Federica Zanetti; Sara Berzuini; Marisol T. Berti (Agronomy, 2020)
Crambe (Crambe abyssinica Hochst) is an oilseed crop in the Brassicaceae family. Crambe’s ability to survive in diverse environmental conditions, its unique oil composition, the high oil content, suitability for the production of slip agents for plasticizers, the capacity to be easily included in common crop rotations, and its adaptability to equipment used for small grain cultivation has renewed the interest in this emerging crop. Crambe is considered one of the main sources of erucic acid, which can be up to 60% of its seed oil content. Erucic acid (C22:1) is a fatty acid with industrial importance since it is used to produce erucamide, key ingredient in the plastic industry. Inclusion of crambe into crop rotations can be beneficial because of its short life cycle, low fertility requirements, resistance to pest and diseases, and relative drought tolerance. Currently high erucic acid rapeseed (Brassica napus L.) (HEAR) is the principal source for erucic acid. However, the risk of contaminating food quality rapeseed (i.e., canola) by cross-pollination and the negative impact on climate, due to high inputs, are potential limitations to expand HEAR cultivation. Crambe has thus great potential to, at least, partially replace HEAR as a source of erucic acid, if the current knowledge-gap in agronomic management and crop improvement (seed yield and quality) can be addressed. Seed yield needs to be increased to be able to compete with HEAR. In addition, reducing glucosinolates and fiber in crambe meal may increase its inclusion in monogastrics rations. The objective of this review was to compile and summarize new and existing information on agricultural practices in crambe production and management to identify gaps in knowledge and areas for future research to increase the cultivation of crambe.